Swallowing function and chronic respiratory diseases: Systematic review - Ghannouchi, I.; Speyer, R.; Doma, K.; Cordier, Reinie; Verin, E. (Elsevier Ltd, 2016)
Background: The precise coordination between breathing and swallowing is an important mechanism to prevent pulmonary aspiration. Factors that alter breathing patterns and ventilation, such as chronic respiratory diseases, may influence that precise coordination of breathing and swallowing. Purpose The purpose of this systematic literature review is to examine the effects of chronic respiratory diseases on swallowing function. Method Literature searches were performed using the electronic databases PubMed and Embase. All articles meeting the eligibility criteria up to March 2016 were included. Results All articles included studied Chronic Obstructive Pulmonary Diseases (COPD) or Obstructive Sleep Apnea (OSA); no studies involving other respiratory diseases were found. A total of 1069 abstracts were retrieved, of which twenty-six studies met the inclusion criteria; eleven studies dealt with OSA and fifteen studies dealt with COPD. Conclusion The outcome data indicate that chronic respiratory diseases increase the prevalence of oropharyngeal dysphagia (OD) in patients. However, the relative small number of studies, differences in selection criteria, definitions and assessment techniques used for diagnosing OSA, COPD, and OD point to the need for further research.